Sestrin-Mediated Inhibition of Stress-Induced Intervertebral Disc Degradation Through the Enhancement of Autophagy - Ji Tu; Wentian Li; Shuai Li; Wei Liu; Yukun Zhang; Xinghuo Wu; Rongjin Luo; Wenbin Hua; Kun Wang; Yu Song; Liang Kang; Wen Yang; et al. (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Intervertebral disc degeneration (IDD) is a pathological process that is the primary cause of low back pain and is potentially mediated by compromised stress defense. Sestrins (Sesn) promote cell survival under stress conditions and regulate AMP-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) signaling. Here, we investigated the expression of Sesn in normal and degraded nucleus pulposus (NP) cells and its potential roles during IDD pathogenesis. Methods: Sesn expression in normal and degraded NP cells was determined by quantitative polymerase chain reaction and immunoblotting and immunohistochemistry, respectively. Sesn function was investigated by using Sesn knockdown and overexpression techniques with analysis of extracellular matrix (ECM), cell apoptosis, autophagy, AMPK, and mTOR activation. Results: In human cultured NP cells, Sesn expression was significantly decreased in degraded NP cells at both the RNA and protein levels. The expression of Sesn1, 2, and 3 increased after stimulation by 2-deoxyglucose (2-DG), an endoplasmic reticulum stress inducer. 2-DG could also increase cell apoptosis, promote extracellular matrix (ECM) degradation, and positively regulate autophagy in NP cells. Sesn knockdown by small interfering RNA increased NP cell apoptosis and ECM degradation under basal culture conditions and in the presence of 2DG. Conversely, Sesn overexpression mediated by plasmid transfection repressed IDD by enhancing autophagy, which was associated with changes in mTOR but not AMPK activation. Conclusions: Sesn expression is suppressed in degraded NP cells. In addition, Sesn inhibits stress-induced cell apoptosis and ECM degradation by enhancing autophagy, which is modulated though mTOR activity. Suppression of Sesn might therefore represent an important cellular dysfunction mechanism in the process of IDD.